Identification of Platelet Antigens by Monoclonal Antibodies Using Crossed Immunoelectrophoresis with Immunoblotting of the Monoclonal Antibody - Thorsen, L I; Gaudernack, G; Brosstad, F; Pedersen, T M; Solum, N O (Thrombosis and Haemostasis, 1987)
A method is described for the identification of antigens by monoclonal antibodies. This is applicable whenever precipitating antibodies to the same antigens from a different species are available. The method is based upon: 1) Separation and immunoprécipitation of cellular proteins with a polyspecific antiserum in crossed immunoelectrophoresis in the presence of the non-denaturing detergent Triton X-100 and the monoclonal antibody. 2) Coprecipitation of the monoclonal antibody with its antigen. 3) Subsequent passive transfer of the monoclonal antibody in the antibody-antigen complex onto a nitrocellulose membrane. 4) Visualization of the blotted antibody using an enzyme-linked secondary antibody and a chromogenic substrate. 5) Identification of the corresponding antigen by comparisons to the immunoprecipitate pattern of the original immunoplate. To test this method we have analyzed the detection of the antigens recognized by six previously described monoclonal antibodies against platelet membrane proteins and von Willebrand factor. Specific immunoblots were obtained in each case using small amounts of monoclonal antibodies. Thus, the technique provides an alternative when epitopes are denatured by SDS, and avoids the use of radioactively labelled monoclonal antibodies.
Keywords: Immunoblotting; Monoclonal antibodies; Crossed immunoelectrophoresis; Platelet antigens